BS IEC 61937-3 AMD1. Digital audio. Interface for non-linear PCM encoded audio bitstreams applying IEC 60958. Part 3. Non-linear PCM bitstreams according to the AC-3 and enhanced AC-3 formats (TA 20) (9th April 2020) - British Standards Institution,
No abstract available